Associations of BMI and obesity with physical literacy, lung capacity, and cardiorespiratory performance in obese adult women - Ali, Mohammad Arif; Kurniawati, Dewi Marfuah; Noer, Etika Ratna; Anggita, Gustiana Mega; Ahda, Zahrah Zakiya; Setyawati, Heny; Kinanti, Rias Gesang; Mukarromah, Siti Baitul; Sugiarto, Sugiarto; Susanto, Hendi; et al. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to: (1) assess the level of physical literacy among obese adult women; (2) evaluate their lung capacity and cardiorespiratory performance; and (3) examine the interrelationships among these variables. A cross-sectional observational study was conducted involving 18 obese adult women in Tegal Regency, Central Java, Indonesia. Participants were assessed for Body Mass Index (BMI), physical literacy using a validated 24-item questionnaire, lung capacity using spirometry, and cardiorespiratory performance using the Six-Minute Walk Test (6MWT). The mean BMI of participants was 31.95±4.26 (Kg/m²), with an average physical literacy score of 76.21±10.01 (moderate level). Lung capacity (FVC) averaged 1.76±0.60 L, and the FEV1/FVC ratio was 82.14±16.63%. Participants completed an average 6MWT distance of 352.08±32.37 meters, indicating reduced cardiorespiratory performance (63.30±6.89% of predicted). Obesity level was significantly correlated with lung capacity, cardiorespiratory performance, and inversely with physical literacy (p<0.05). BMI showed significant negative correlation with physical literacy (p<0.05), but not with lung capacity (p>0.05). Most participants retained normal lung function despite obesity. Obese adult women in this study generally demonstrated moderate physical literacy and average lung and cardiorespiratory function. Obesity level, more than BMI alone, was a stronger predictor of reduced lung capacity and physical performance. Findings highlight the importance of integrating physical literacy into gender-responsive obesity interventions.